Research on the evolution and influencing factors of the spatial form of typical tourist towns: a case study of Wulingyuan district, China - Long, Tengzhe; Luo, Bincheng; Wu, Jilin; Yang, Jing; Wang, Yunzhe (Frontiers in Environmental Science, 2025)
IntroductionSince its reform and opening up, China’s new urbanization strategy, which provides institutional support for the optimization of the spatial form of tourism towns, has made remarkable progress and demonstrated great potential. In this study, the urban area of Wulingyuan District, China, a Natural World Heritage Site, is taken as the research object.MethodsBased on Landsat remote sensing images at five time nodes between 2000 and 2022, the spatial and temporal characteristics and evolutionary patterns of urban expansion in Wulingyuan are quantitatively investigated and the driving factors are explored using fractal theory, the equal sector analysis method, partial least squares regression (PLSR), and the standard deviation ellipse.ResultsThe results reveal the following. (1) From 2000 to 2022, urban expansion has undergone four clear stages, namely, medium-speed, low-intensity, low-speed, low-intensity, medium-speed, medium-intensity, and medium-speed, high-intensity. The period from 2015 to 2022 represents the peak of urban expansion. (2) The built-up land in the urban area has mainly expanded in the form of a belt. The overall direction of expansion tends to be in the southwest and northeast directions, while expansion in the other directions has occurred slowly due to terrain and heritage protection restrictions. (3) In terms of the evolution of spatial forms, the compactness index of the urban area has exhibited a “V”-shaped change, the fractal dimension has continued to decline, and the expansion pattern has undergone three stages: edge expansion dominance, parallel edge expansion and internal infilling, and internal infilling dominance. (4) The urban expansion of Wulingyuan has been driven by multiple factors such as urbanization, tourism, the economy, and policy. The intensity of the roles of these factors, from strongest to weakest, is as follows: urbanization > tourism > economy.DiscussionPolicy factors do not directly promote urban expansion, but rather enforce control over the direction, scale, and boundaries of urban expansion through the dual effects of positive guidance and negative constraints. Based on the results of this study, a conservation-oriented development (COD) path is proposed, aiming to provide a replicable model for other heritage cities or those characterized by ecologically sensitive tourism.